PENGARUH KARAKTERISTIK INDIVIDU DAN KARAKTERISTIK PEKERJAAN TERHADAP KEPUASAN KERJA IMPLIKASINYA PADA KOMITMEN PEGAWAI (Studi Kasus pada Dinas Pekerjaan Umum Kabupaten Pidie Jaya) - Ery Puspita; Fauzi Fauzi; Mahyu Danil (LPPM-UNIKI, 2026)
This study examines employee job satisfaction, which impacts commitment based on individual and job characteristics. The study was conducted on employees of the Public Works Department of Pidie Jaya Regency, Aceh. The quantitative associative method was used, and the hypothesis was tested using path analysis as a statistical tool. The study found: (1) Individual and job characteristics, through job characteristics, have a direct and indirect effect on employee job satisfaction, amounting to 45.24% and 46.87%, respectively. (2) Individual and job characteristics simultaneously contribute to changes in employee job satisfaction by 54,8%. (3) Job satisfaction factors have a 63.7% effect on employee commitment. (4) There is a causal relationship between individual and job characteristics, with a fairly strong category (57.7%), which has direct and indirect implications for employee commitment, amounting to 28.49% and 30.67%, respectively. (5) Individual and job characteristics simultaneously have a positive impact of 78,1% on employee commitment at the Pidie Jaya Public Works Department.